2021
DOI: 10.1186/s13046-021-02143-x
|View full text |Cite
|
Sign up to set email alerts
|

Lnc-RP11-536 K7.3/SOX2/HIF-1α signaling axis regulates oxaliplatin resistance in patient-derived colorectal cancer organoids

Abstract: Background Resistance to oxaliplatin is a major obstacle for the management of locally advanced and metastatic colon cancer (CC). Although long noncoding RNAs (lncRNAs) play key roles in CC, the relationships between lncRNAs and resistance to oxaliplatin have been poorly understood yet. Methods Chemo-sensitive and chemo-resistant organoids were established from colon cancer tissues of the oxaliplatin-sensitive or -resistant patients. Analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 55 publications
1
33
0
Order By: Relevance
“…Recent studies have focused on the function of tumor metabolism, especially glycolysis, which is reported to play a role in promoting tumor drug resistance [ 10 , 11 , 12 ]. GEM-R bladder cancer cells showed increased glucose uptake, lactate production, and cell medium acidification ( Figure 5 D).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have focused on the function of tumor metabolism, especially glycolysis, which is reported to play a role in promoting tumor drug resistance [ 10 , 11 , 12 ]. GEM-R bladder cancer cells showed increased glucose uptake, lactate production, and cell medium acidification ( Figure 5 D).…”
Section: Resultsmentioning
confidence: 99%
“…Chemo‐resistance of cancer cells is influenced by the activity of lncRNAs. 238 , 239 A recent study has revealed lncRNA ANRIL enhanced cancer resistance by promoting homologous recombination‐mediated DNA repair. 240 In addition, LINC00842 promoted malignancy through metabolic remodeling.…”
Section: Lncrnas and Circrnas In Neuroblastomamentioning
confidence: 99%
“…LINC00092 binds 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 2 (PFKFB2) and thus promotes malignant metastasis of OC by altering glycolysis and maintaining the local support function of cancer-associated fibroblasts (CAF) ( Zhao et al, 2017 ; Hashemipour et al, 2021 ). Li et al, revealed that CTSLP8 expression increases in chemoresistant tumor tissues, which promotes c-Myc expression and thus upregulates glycolysis by facilitating the binding of PKM2 to the c-Myc promoter region ( Li Q et al, 2021 ). Yang et al, demonstrated that LINC00035 promotes malignant progression of OC by regulating glycolysis and apoptosis through CEBPB-mediated SLC16A3 transcription ( Yang et al, 2021 ).…”
Section: The Regulatory Mechanism Of Ncrnas In the Glycolysis Of Ovar...mentioning
confidence: 99%
“…NcRNAs are involved in a variety of life activities such as regulation of gene expression, intracellular signaling and epigenetic modifications. Apart from participation in tumorigenesis, ncRNAs also account paramount role in the glycolytic process of tumors ( Li Q et al, 2021 ; Lu et al, 2021 ; Park et al, 2021 ; Razavi et al, 2021 ; Wang et al, 2021 ). This review summarizes the possible molecular mechanisms of ncRNAs in the process of glycolysis and potentially effective targeted therapies for OC.…”
Section: Introductionmentioning
confidence: 99%